Radiological Outcome of Scaphoid Nonunion treated with modified Matti-Russe Technique. (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the radiological outcome of Scaphoid nonunion treated with modified Matti-Russe technique.Methods: This descriptive study was conducted in Department of Orthopedics Khyber teaching hospital Peshawar from 23rd June 2017 to 23rd June 2020. All patients with Scaphoid nonunion fulfilling the inclusion criteria were treated with modified Matti-Russe technique. Regular follow up was done and radiological union was confirmed with X ray wrist AP and lateral View.Results: The total number of patients enrolled in our study were 16. Male patients were 14(87.5%) and female were 2(12.5%). Mean age was 32.5±5.87 years. Right sided scaphoid non union was present in 10(62.5%) patients and left in 6(37.5%) patients. Mean time since fracture at presentation was 17 ±4.49 weeks(range 12 to 18.3 weeks).Post operatively all patients achieved radiological union. The average union time was 15±2.5 weeks (range 13.4 to 16 weeks). No major complication noted.Conclusion: Modified Matti-Russe technique is a reliable option for the treatment of Scaphoid nonunion as it showed high percentage of healing in our series. We therefore recommend this technique as treatment of choice to treat Scaphoid non union.